Analyzing the impact of quarantine and asymptomatic infection on the transmission dynamics of Covid-19 - Ujunwa Chikwelu, Chinelo; Ibezimako Mbegbu, Julian; Ewere, Friday (Brazilian Journal of Biometrics, 2026)
The global rapid spread of COVID-19, partially driven by asymptomatic undetected carriers, needs appropriate modeling to inform effective intervention strategies. This research develops and describes a deterministic compartmental model with six epidemiological classes: Susceptible (S), Exposed (E), Asymptomatic Infected (IA), Symptomatic Infected (IS), Quarantined (Q), and Recovered (R), all encompassing the SEIAISQR framework. The model incorporates the progression of asymptomatic infections to symptomatic phases prior to progressing into quarantine, which captures realistic disease state progressions. By means of analytical methods, the basic reproduction number (R0) is derived from the nextgeneration matrix, and the local and global stability of the disease-free steady state are established under the R0 < 1 assumption. Sensitivity analysis reveals that transmission rates, progression rates, and quarantine policies drive R0, and transmission through asymptomatic carriers is dominant. Euler’s method-based numerical simulation shows that asymptomatic undetected carriers have a high contribution to persistent disease transmission, while effective quarantine and extensive recovery severely inhibit epidemic persistence. This paper stresses the critical necessity for robust public health measures involving mass testing, successful contact tracing, and isolation of asymptomatic patients in a bid to combat COVID-19.